TRANSFORMATION OF SOCIAL BEHAVIOR ACTIVIST ASSEMBLY OF TAKLIM AND PRAYER - Alisha, Moh Nafi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand the Development of Digital Literacy-Based Animation Video Media to Stimulate Language Ability in Early Childhood. This study uses the Research and Development development model. Data analysis techniques consist of validation data analysis, practicality data analysis, attractiveness data analysis, and data analysis on the effectiveness of animated video products. The results of the percentage validity of the media, the results of individual trials, the results of small group trials and the results of large group trials were included in the very practical, interesting and effective categories. Based on the results of the validity of material experts, media experts, linguists and instruments that have been filled in to determine the level of practicality, attractiveness and effectiveness, digital literacy-based animated video media is appropriate and appropriate for use in the process of learning activities to stimulate language skills in early childhood. This article aims to describe the transformation of the social behavior of youth activists of taklim and prayer groups in carrying out the role of education and da'wah in Indonesia. The role of majlis taklim and prayer is very large in spreading the values of Islamic da'wah. Majlis taklim and sholawat have become a forum for Islamic education that has survived to this day both in rural and urban areas, especially in areas where there are many young people. One of the majlis taklim and sholawat in Banyuwangi is Laskar Langit (LL) as a da'wah system for the majlis taklim and sholawat in Banyuwangi Regency. Da'wah is usually carried out only to people who have middle to upper religious knowledge. As for those with dark backgrounds, there are still very few Dais who focus their da'wah on these people. In fact, Muslims who live in a world of disobedience also have the desire to return to the right path. Laskar Langit is here to provide a place for those who want to repent through sholawat media. If the Islam of the members of the Sky Warriors community has really changed, has changed to become a better human being, it must have gone through a long process. The social construction of Islam is a social reality of daily life regarding the basic teachings of Islam which are understood in a dialectical process. Namely there is externalization, objectivation, and internalization. The results of this study indicate that the da'wah of the majlis taklim and sholawat uses various media including declaring the names of the communities in each region, collaborating between hadroh and local music. The implication of this research is that policy makers in the taklim assembly and sholawat must understand new ways of nurturing and inviting youth to remain istiqomah in carrying out worship.